Digital Ecclesiology and Hybrid Worship in Post-Pandemic Indonesian Religious Communities - Samsul Ode; Kushandajani Kushandajani; Yuwanto Yuwanto; Wijayanto Wijayanto (UIN Sunan Gunung Djati Bandung, 2025)
The COVID-19 pandemic fundamentally altered religious practices in Indonesia, accelerating a transition toward hybrid worship models that combined physical and digital formats. Despite the end of pandemic-related restrictions, digital participation continued to grow, raising critical questions about its long-term implications for spiritual depth, social cohesion, and ritual sacredness. This study aimed to analyze the transformation of religiosity by examining shifts in community engagement patterns resulting from the move to digital formats, and to evaluate the psychosocial impact of online worship on spiritual meaning and interpersonal connection in a post-pandemic context. A descriptive qualitative method was employed, utilizing semi-structured in-depth interviews with 20 purposively selected interfaith informants across urban settings in Jakarta and rural settings in Alor (East Nusa Tenggara) and Rembang (Central Java). Data saturation guided sample size determination, and thematic analysis was applied following verbatim transcription and rigorous coding. The findings revealed a pronounced digital divide: urban communities particularly those with pre-pandemic infrastructure readiness, such as the Seventh-day Adventist community demonstrated proactive technological adoption, whereas rural communities were constrained by limited connectivity and reverted to physical gatherings. Based on qualitative coding of interview data, twelve of the twenty informants expressed that digital worship lacked a sense of sacredness, mainly due to the absence of physical sanctity and collective presence. Technology was perceived primarily as a functional transmission tool rather than a self-sustaining sacred space. The study concluded that while digital platforms enhanced accessibility for specific groups, the permanent shift toward hybrid worship risks spiritual alienation and weakens Durkheimian social solidarity without adequate mediation strategies. A theological redefinition through the concept of Digital Ecclesiology was recommended to maintain sacredness and inclusivity within hybrid faith ecosystems. This study contributes to the literature on digital religion by conceptualizing Digital Ecclesiology as a framework for understanding sacredness, inclusivity, and communal solidarity in hybrid worship ecosystems.